EMODnet Workshop on mechanisms and guidelines to mobilise historical data into biogeographic databases - Sarah Faulwetter; Evangelos Pafilis; Lucia Fanini; Nicolas Bailly; Donat Agosti; Christos Arvanitidis; Laura Boicenco; Terry Capatano; Simon Claus; Stefanie Dekeyzer; Teodor Georgiev; Aglaia Legaki; et al. (Research Ideas and Outcomes, 2016)
The objective of Workpackage 4 of the European Marine Observation and Data network (EMODnet) is to fill spatial and temporal gaps in European marine species occurrence data availability by carrying out data archaeology and rescue activities. To this end, a workshop was organised in the Hellenic Center for Marine Research Crete (HCMR), Heraklion Crete, (8–9 June 2015) to assess possible mechanisms and guideCorrespondinglines to mobilise legacy biodiversity data. Workshop participants were data managers who actually implement data archaeology and rescue activities, as well as external experts in data mobilisation and data publication. In particular, current problems associated with manual extraction of occurrence data from legacy literature were reviewed, tools and mechanisms which could support a semi-automated process of data extraction were explored and the re-publication of the data, including incentives for data curators and scientists were reflected upon.